Innovative Mobile Learning 2009
DOI: 10.4018/978-1-60566-062-2.ch012
|View full text |Cite
|
Sign up to set email alerts
|

An Architecture for a Personalized Mobile Environment to Facilitate Contextual Lifelong Learning

Abstract: In response to the ever-increasing need of private and public organizations for lifelong learning, research in technology-enhanced learning has been geared towards the provision of systems that will better support those who pursue education at a number of different stages in their life, move between institutions while pursuing a course of study, or make use of resources and facilities from more than one institution/ organization. The new generation of mobile phones can support applications that would facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mobile computing technology provides learners with unprecedented opportunities for communicating, interacting, sharing, meaning-making, and content and context generation (Cook & Pachler, 2012). Mobile learning, or m-learning, will play a vital role in the rapidly growing electronic education market (Dimakopoulos & Magoulas, 2009;Wang, Wu, & Wang, 2009). RnRMarke-tResearch.com (April 2015) predicted that the worldwide market for m-learning applications (apps) will grow from US$7.98 billion in 2015 to US$37.60 billion by 2020 and mushroom to US$325 billion by 2025, with a compound annual growth rate (CAGR) of over 7%.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile computing technology provides learners with unprecedented opportunities for communicating, interacting, sharing, meaning-making, and content and context generation (Cook & Pachler, 2012). Mobile learning, or m-learning, will play a vital role in the rapidly growing electronic education market (Dimakopoulos & Magoulas, 2009;Wang, Wu, & Wang, 2009). RnRMarke-tResearch.com (April 2015) predicted that the worldwide market for m-learning applications (apps) will grow from US$7.98 billion in 2015 to US$37.60 billion by 2020 and mushroom to US$325 billion by 2025, with a compound annual growth rate (CAGR) of over 7%.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that personal mobile technologies have a role in sustaining and promoting lifelong learning more generally (e.g. Dimakopoulos and Magoulas, 2009). However, in order to understand how best to support mobile language learners, we need to understand learner practices, across both formal and informal settings.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that the size of a learner's vocabulary is strongly associated with their reading and writing abilities (Staehr, 2008). The use of technologies in language learning support lifelong and contextual vocabulary learning (Dimakopoulos & Magoulas, 2009) and is becoming more popular among language learners. A review on language learning applications showed that vocabulary instruction was the main focus of 84% of the reviewed language learning applications.…”
Section: Informal Vocabulary Learning Using Technologiesmentioning
confidence: 99%